2004
DOI: 10.1111/j.1600-0501.2004.01027.x
|View full text |Cite
|
Sign up to set email alerts
|

Cement fixation and screw retention: parameters of passive fit

Abstract: It is generally assumed that passively fitting superstructures are a prerequisite for long-lasting implant success. In the study presented, the strain development of three-unit implant fixed partial dentures (FPDs) was evaluated at the bone surrounding the implant and on the superstructure using a strain gauge technique. Six groups of three-unit FPDs representing the commonly used techniques of bridge fabrication were investigated with 10 samples each, in order to quantify the influence of impression technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
83
1
20

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(115 citation statements)
references
References 20 publications
6
83
1
20
Order By: Relevance
“…These results corroborate previous studies 8,12,13,16,27,28,29 which demonstrated that no metallic framework presents perfect fit. Despite the advanced technology, the material and techniques performed for fabrication of prostheses are not dimensionally accurate and require further research and development 6,15 .…”
supporting
confidence: 83%
See 2 more Smart Citations
“…These results corroborate previous studies 8,12,13,16,27,28,29 which demonstrated that no metallic framework presents perfect fit. Despite the advanced technology, the material and techniques performed for fabrication of prostheses are not dimensionally accurate and require further research and development 6,15 .…”
supporting
confidence: 83%
“…The accomplishment of five measurements per sample, for both groups, at the three moments, aimed to minimize errors. High standard deviation values were recorded, similar to previous reports 28 , probably due to the high sensitivity of strain gauges when compared to the forces yielded in the system. It should be noted that despite the search for standardization, each metallic framework was a unique structure which implies unpredictable three-dimensional alterations.…”
supporting
confidence: 73%
See 1 more Smart Citation
“…Quanto ao posicionamento linear dos extensômetros, este trabalho está de acordo com Heckmann et al 19 , que estudaram deformações ao redor de implantes com estruturas metálicas A qualidade óssea é um fator de importância na eficácia do tratamento com implantes. O osso que os circunda não constitui um substrato homogêneo, de modo que suas propriedades físicas variam conforme a idade, o estado funcional e os fatores sistêmicos do paciente 7 .…”
Section: Discussionunclassified
“…Electrical strain gauges are used to determine stress and deformation measurements in relation to the forces exerted on implants, and their transfer to the supporting structures [21][22][23][24][25]. The method is based on the use of electrical strain gauges, small electrical resistances that change the resistance to low intensity current, which detects the slightest deformation in the structure evaluated.…”
Section: Introductionmentioning
confidence: 99%